Dampak Ekonomi Insentif PPN DTP Perumahan dan PPNBM DTP Kendaraan Bermotor pada Masa Pandemi - Silaban, Wiradinata Lambok; Irawan, Ferry (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2024)
The economic downturn caused by the pandemic, prompted the Indonesian government to produce fiscal policy in government-borne tax incentive scheme to stimulate economic growth. This study aimed to find out whether the real estate sector and the processing industry sector do have a big impact on the economy and to determine the quantitative economic impact as an implication of government-borne value-added tax for houses and government-borne sales tax on luxury goods for motor vehicle of IDR5.202 trillion in 2021 in terms of output, labor, and VAT potential and provide suggestions related to tax incentives. This study used input-output analysis with Indonesian IO Table tool of 2016 which was updated to IO Table of 2021 using RAS method. The data used are secondary data published by Central Bureau of Statistics and Fiscal Policy Agency. The results of the analysis showed that the real estate sector does not have a big influence on the economy, but the processing industry sector gives a big influence. The study also found that the impact of tax incentives was able to create increases in total output of IDR8.884 trillion, employment of 37,174 people, and potential VAT of IDR0.463 trillion. The results of this study suggest the government to consider the priority of providing incentives more directed and measurable by adjusting the objectives of the incentives and targeted sectors, paying attention to strategic and alternative sectors, and continuing the government-borne tax incentive scheme in the event of an economic slowdown.